A Case for a Critical Examination of Diagnostic Delays Among Women - Gregory, Kelly; Pritlove, Cheryl; Upshur, Ross; Kontos, Pia (Aporia, 2025)
This work offers a critical examination of research which investigates the reasons behind diagnostic delays among women, to recognize that the phenomenon has been insufficiently understood and poorly theorized. We then call for a deeper understanding of women’s embodied lived experience of diagnostic delays, as well as of the social and political contexts that are shaping and reproducing these delays. To address this task, we end by describing and proposing the theoretical engagement of critical phenomenology, for its capacity to consider the full complexity of this wicked and enduring problem.